2014
DOI: 10.1016/j.mex.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel detection method for chemiluminescence derived from the Kinase-Glo luminescent kinase assay platform: Advantages over traditional microplate luminometers

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The simplicity of measuring luminescence can be taken advantage of since other types of equipment, such as CCD cameras, can convert light emitted from a luminescent reaction to a digital signal for quantification. Previously it was shown that a Western-blot imaging system can be adapted to reliably detect and quantify luminescent signals [3] . Expanding the use of a common piece of laboratory equipment such as this can be preferable to purchasing a dedicated luminometer, if one is not already present.…”
Section: Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplicity of measuring luminescence can be taken advantage of since other types of equipment, such as CCD cameras, can convert light emitted from a luminescent reaction to a digital signal for quantification. Previously it was shown that a Western-blot imaging system can be adapted to reliably detect and quantify luminescent signals [3] . Expanding the use of a common piece of laboratory equipment such as this can be preferable to purchasing a dedicated luminometer, if one is not already present.…”
Section: Methods Detailsmentioning
confidence: 99%
“…If needed, the sensitivity could be increased further by increasing the exposure time, or increasing pixel-binning. We chose to use black microplates to stay consistent with previous methods [3] , however white microplates are often recommended for luminescent assay as they reflect light more efficiently, resulting in greater sensitivity.…”
Section: Additional Informationmentioning
confidence: 99%
“…It also allows higher ATP concentrations (up to 500 μM), thus making it more versatile. 71 , 93 , 97 , 98 ADP-Quest differs from the two kits described above as it measures fluorescence. ADP-Quest exploits the ADP produced in the kinase reaction to convert 10-acetyl-3,7-dihydroxyphenoxazine (ADHP), a fluorescent dye precursor the fluorescent resorufin.…”
Section: In Vitro Assays For the Evaluation Of Lsrk Activitymentioning
confidence: 99%
“…This assay’s advantages include a more stable luminescence signal and shorter analysis time, making it suitable for the screen of large compound libraries. It also allows higher ATP concentrations (up to 500 μM), thus making it more versatile. ,,, ADP-Quest differs from the two kits described above as it measures fluorescence. ADP-Quest exploits the ADP produced in the kinase reaction to convert 10-acetyl-3,7-dihydroxyphenoxazine (ADHP), a fluorescent dye precursor the fluorescent resorufin.…”
Section: In Vitro Assays For the Evaluation Of Lsrk Activitymentioning
confidence: 99%